A Six Months Analysis of COVID-19 Death : Experience From a Tertiary Hospital, Chattogram (Journal of Chittagong Medical College Teachers' Association, 2022)
Background : COVID 19 pandemic had taken away lots of human life prematurely worldwide and death laid its icy hands also on Bangladesh. So, objectives of this study were to explore the monthly distributions, age, sex, comorbidities, localities and duration of hospital stay among the COVID 19 death cases.  Materials and methods: In this observational study six months hospital death registries were collected and explored for monthly distributions, age, sex, comorbidities, localities and hospital stay.  RT-PCR positive confirmed 113 COVID deaths were enrolled and suspected COVID deaths were excluded. Ethical clearance from the hospital authority was taken before hand. Data was compiled and analyzed by SPSS-20.Results: There was a low frequency of death in the months May-2021 and October-2021(7.1% and 2.7% respectively) but more during June -2021 to September 2021 (12.4%, 16.8%, 42.5% and 18.6% respectively). Female deaths were   more than male deaths (53.1% vs 46.9%, p